2021
DOI: 10.3390/ijms22031261
|View full text |Cite
|
Sign up to set email alerts
|

Immunopathogenicity of Acanthamoeba spp. in the Brain and Lungs

Abstract: Free-living amoebas, including Acanthamoeba spp., are widely distributed in soil, water, and air. They are capable of causing granulomatous amebic encephalitis, Acanthamoeba pneumonia, Acanthamoeba keratitis, and disseminated acanthamoebiasis. Despite low occurrence worldwide, the mortality rate of Acanthamoeba spp. infections is very high, especially in immunosuppressed hosts. Acanthamoeba infections are a medical problem, owing to limited improvement in diagnostics and treatment, which is associated with inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
26
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 126 publications
3
26
0
3
Order By: Relevance
“…also cause granulomatous amoebic encephalitis (GAE). It is an opportunistic, rare disease with a mortality rate of 97-98% [135,136]. Infection occurs by inhalation of air or water aspiration containing invasive forms of Acanthamoeba spp.…”
Section: Acanthamoeba Sppmentioning
confidence: 99%
See 1 more Smart Citation
“…also cause granulomatous amoebic encephalitis (GAE). It is an opportunistic, rare disease with a mortality rate of 97-98% [135,136]. Infection occurs by inhalation of air or water aspiration containing invasive forms of Acanthamoeba spp.…”
Section: Acanthamoeba Sppmentioning
confidence: 99%
“…Infection occurs by inhalation of air or water aspiration containing invasive forms of Acanthamoeba spp. Severe headaches, neck pains, confusion, irritability, hallucinations, fever, nausea, and vomiting have been observed in GAE patients [135,136]. Due to the difficult, often long-term diagnosis of granulomatous encephalitis, treatment of this disease is problematic [129,137].…”
Section: Acanthamoeba Sppmentioning
confidence: 99%
“…Acanthamoeba spp., infection of the lungs occurs mostly in immunosuppressed patients (Kaul et al 2008 ). According to previous studies, 19 cases of AP or disseminated acanthamoebiasis with lung infection were reported (Kot et al 2021 ). These patients had a history of acute and chronic marrow leukemia, acute myeloblastic leukemia, acute lymphoblastic leukemia, chronic myelogenous leukemia, atypical pneumonia, and organ transplant recipients (Kot et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…According to previous studies, 19 cases of AP or disseminated acanthamoebiasis with lung infection were reported (Kot et al 2021 ). These patients had a history of acute and chronic marrow leukemia, acute myeloblastic leukemia, acute lymphoblastic leukemia, chronic myelogenous leukemia, atypical pneumonia, and organ transplant recipients (Kot et al 2021 ). However, according to the literature review, Vernon et al reported a case of Acanthamoeba infection in a lung transplant patient, who presented with rhinosinusitis (Vernon et al 2005 ).…”
Section: Introductionmentioning
confidence: 99%
“…Optimal approach to the treatment of this disease is uncertain. Only a few reports of successful treatment with combination drug therapy are available in the literature; the following drugs were used in various combinations for variable durations ranging from two weeks to several months: miltefosine, fluconazole, ketoconazole, trimethoprimsulfamethoxazole, sulfadiazine, metronidazole, rifampicin, vancomycin, ceftriaxone, dexamethasone, albendazole, carbamazepine, pentamidine, liposomal amphotericin B, flucytosine, and voriconazole ([9] Kot et al, 2021).…”
Section: Introductionmentioning
confidence: 99%